Methylene Blue Photodegradation under Visible Irradiation on Ag-Doped ZnO Thin Films (2019)
This study synthesized and characterized Ag-doped ZnO thin films. Doped ZnO powders were synthesized using the sol-gel method, and thin films were fabricated using the doctor blade technique. The Ag content was determined by optical emission spectrometers with inductively coupled plasma (ICP plasma). Additionally, X-ray diffraction, Raman spectroscopy, Atomic Force Microscopy (AFM), diffuse reflectance, and X-ray photoelectron spectroscopy (XPS) measurements were used for physicochemical characterization. Finally, the photocatalytic degradation of methylene blue (MB) was studied under visible irradiation in aqueous solution. The Langmuir-Hinshelwood model was used to determine the reaction rate constant of the photocatalytic degradation. The physicochemical characterization showed that the samples were polycrystalline, and the diffraction signals corresponded to the ZnO wurtzite crystalline phase. Raman spectroscopy verified the ZnO doping process. The AFM analysis showed that roughness and grain size were reduced after the doping process. Furthermore, the optical results indicated that the presence of Ag improved the ZnO optical properties in the visible range, and the Ag-doped ZnO thin films had the lowest band gap value (2.95 eV). Finally, the photocatalytic degradation results indicated that the doping process enhanced the photocatalytic activity under visible irradiation, and the Ag-doped ZnO thin films had the highest MB photodegradation value (45.1%), as compared to that of the ZnO thin films (2.7%).